COOPERATIVE DETERMINATION OF OCTANE REQUIREMENT FOR CAR POPULATIONS IN ASEAN COUNTRIES - A.S. Nasution (Scientific Contributions Oil and Gas, 1987)
The supply of motor gasoline at the correct octane level is of utmost importance to every country since it bears economic and technical consequences in the cost of energy supply and in the maintenance and replacement costs of engines.  The determination of the actual octane requirement of the existing car population, on the other hand, is a tedious an costly activity.  Better results and less cost could be incurred through a cooperative approach by several countries.  The paper describes the significance of octane requirement, its method of measurement, and presents the results for Indonesia.  Based on this experience a strong recommendation is made for a cooperative determination of octane requirement in the ASEAN region.